Reduced mitochondrial size in hippocampus and psychiatric behavioral changes in the mutant mice with homologous mutation of Timm8a1-I23fs49X - Ouattara, Niemtiah; Chen, Zirui; Huang, Yihua; Chen, Xia; Song, Pingping; Xiao, Zhongju; Li, Qi; Guan, Yuqing; Li, Ziang; Jiang, Yawei; Xu, Kaibiao; Pan, Suyue; et al. (Frontiers in Cellular Neuroscience, 2022)
Abstract Background Deafness-dystonia-optic neuronopathy (DDON) syndrome, a condition that predominantly affect males, is caused by mutations in TIMM8A/DDP1 gene and characterized by progressive deafness coupled with other neurological abnormalities. In a previous study, we demonstrated the phenotype of the male mice carrying the hemizygous mutation of Timm8a1-I23fs49X. In follow-up to that study, the current study aimed to observe the behavioral changes in the female mutant (MUT) mice with homologous mutation of TIMM8A and to elucidate the underlying mechanism for the behavioral changes. Methods Histological analysis, transmission electron microscopy (EM), Western blotting, hearing measurement by auditory brainstem response and behavioral observation were compared between the MUT mice and wild-type (WT) littermates. Results The weight of the female MUT mice was lesser than that of the WT mice. Among MUT mice, both male and female showed hearing impairment, anxiety-like behavior by elevated plus maze test, and cognitive deficit by Morris water test. Furthermore, the female MUT mice exhibited coordination problems in the beam balance test. Although general neuronal loss was not found in the hippocampus of the MUT genotype, EM assessment indicated that the mitochondria size showing as aspect ratio and form factor in the hippocampus of the MUT strain was significantly reduced compared to that in the WT genotype. More important, this phenomenon was correlated with the upregulation of translation of mitochondrial fission process 1 (MTFP1)/ mitochondrial fission process 1,18 kDa (MTP18), a key fission factor which is a positive regulator of mitochondrial fission and mitochondrial size. Interestingly, significantly reductions in the size of the uterus and ovaries were noted in the female MUT mice, which contributed to significantly low fertility in the MUT mice. Conclusions Together, homologous mutation in Timm8a1 gene caused hearing impairment, psychiatric behavioral changes in the MUT mice; the latter phenotype might be related to reduction in mitochondria size regulated by MTP18.